2019
DOI: 10.1007/s00425-019-03168-5
|View full text |Cite
|
Sign up to set email alerts
|

Nectar composition in moth-pollinated Platanthera bifolia and P. chlorantha and its importance for reproductive success

Abstract: Main conclusion Sugars (glucose, fructose and sucrose), as well as proteogenic and non-proteogenic amino acids, are present in the nectar of Platanthera bifolia and P. chlorantha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 93 publications
2
27
1
Order By: Relevance
“…Most of the 29 AAs that were present in the nectar of P. caeruleum often occur in the nectar of other plant species [ 13 , 15 , 42 , 49 , 50 ]. In addition to AAs common in floral nectar, our analysis also revealed the presence of sarcosine, tryptophan, and norvaline, which have been rarely reported in earlier analyses [ 20 , 50 , 51 ]. However, even the effect of well-known AAs on pollinators is often not known.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Most of the 29 AAs that were present in the nectar of P. caeruleum often occur in the nectar of other plant species [ 13 , 15 , 42 , 49 , 50 ]. In addition to AAs common in floral nectar, our analysis also revealed the presence of sarcosine, tryptophan, and norvaline, which have been rarely reported in earlier analyses [ 20 , 50 , 51 ]. However, even the effect of well-known AAs on pollinators is often not known.…”
Section: Discussionsupporting
confidence: 73%
“…Our analysis revealed that the mean content of AAs in nectar samples was 590.3 ± 1006 pmol/µL and it did not differ among populations. However, despite the lack of significant differences in AA concentration, we found significant variation in nectar AA composition between study populations ( Table 1 , Supplementary Materials Table S3 ), as has been presented for other plant species [ 12 , 13 , 14 , 20 , 46 ]. On the other hand, when considering the differences between the three designated geographical regions, there were no observed trends in the AA profile, despite that the percentage share of glutamine varied significantly.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations